A randomized controlled efficacy trial of a smoking prevention programme with Grade 8 students in high schools. (2019) - Thurston, Allen; Dunne, Laura; Kee, Frank; Gildea, Aidean; Craig, Nicole; Stark, Patrick; Lazenbatt, Anne
Highlights: This research reports on a smoking prevention Level 3 efficacy trial with Grade 8 high-school students. The intervention relied on developing resilience to peer and advertiser pressure. The programme prevented smoking commencement in intervention schools. Smoking was measured using exhaled breath carbon monoxide and did not rely on self-reported measures. Abstract: The study undertook a Level 3 efficacy trial of a smoking prevention programme in Grade 8 high-school classrooms. A smoking prevention programme, 'Dead Cool', was tested in a randomized controlled trial. 17 Grade 8 classes were randomly assigned to intervention or control arms of the trial. The intervention was a cooperative learning-based intervention of five, 40 min lessons delivered by teachers, but designed by Cancer Focus NI. The primary outcome was smoking as measured by carbon monoxide (CO) in exhaled breath. Measurements of CO were undertaken pre-test, immediately post-test and three months after the intervention. Multi-level modelling indicated the programme prevented smoking initiation in Grade 8 students. Implications for research and design of school-based smoking prevention programmes are discussed.